ANALYSIS OF ESSENTIAL FATTY ACIDS IN LIPID OF THE TROPICAL MARINE MICROALGAE NANNOCHLOROPSIS SP. - BERLIANA SEPTIANI (NIM: 10512013), MAYANG
The demand of essential fatty acids for food increases annually. To date, fish oils which are a major of essential oil sources have no longer fulfil the demand. Hence, efforts to find a new organism producing essential oils such as from microalgae are essential. The research aimed to determine fatty acid content in lipid of the tropical marine microalgae Nannochloropsis sp. The research methods included cultivation of Nannochloropsis sp. in sea water enriched by Walne medium, extraction of lipid by the method of Bligh and Dyer, characterization of lipid content by thin layer chromatography (TLC) method, and determination of fatty acid content in the lipid by gas chromatography-flame ionization detector (GC-FID). The results showed the dried biomass of Nannochloropsis sp. cultivated with an initial cell density of 500,000 cell/mL in a culture volume of 3 L for eight days was in a range of 0.50Ã‚Â–1.05 g. Nannochloropsis sp. cells had 17.03% total lipid content, containing ester cholesterol, triacylglycerol, free fatty acid, diacylglycerol, monoacylglycerol, and phospholipid. The fatty acid content found in Nannochloropsis sp lipid was saturated fatty acids (C8, C12, C13, C14, C15, C16, C17, C18, C19, C20, C22, and C23), monounsaturated fatty acids (C14:1, C16:1, and C18:1n9c), and polyunsaturated fatty acids (C18:2n6c, C18:3n3, C20:3n6, and C22:6n3). The essential fatty acids of Nannochloropsis sp. were linoleic acid (C18:2n6c), linolenic acid (C18:3n3), and docosahexanoic acid (C22:6n3, DHA) with total amount of 0.041, 0.069, and 0.396 mg, in 30.02 mg lipid.